Digital Diplomacy in Russian International Studies: Research Methods - A. A. Pavlyuchenko (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика, 2025)
In the last decade, digitalization has had an increasing impact on the world political processes and is turning into an integral element of international life. Diplomatic practice, given the growing importance of the digital diplomacy, is no exception. In this context, the need for continuous improvement of the methods of studying these processes and phenomena is all the more pressing. This paper examines the key methods used in Russian studies on digital diplomacy, and identifies their strengths and weaknesses. The first section of the article covers publications built on the discourse analysis of small texts on international policy or their excerpts. The author concludes that such an approach allows for a correct description of the communication strategies of various political players. However, it is more suitable for linguistic research, since it does not address the issues crucial for political scientists, namely those concerning the evaluation of the effectiveness of digital diplomacy tools. The second section considers the research works based on the content analysis. The author argues that although this method provides an opportunity to process a larger amount of data and to reduce the impact of subjective factors, it has its limitations, particularly, inability to take into account the visual component of publications and to place them within a wider information context. The third section focuses on the scholarly papers drawing on the most time-consuming and demanding method of Big Data (hashtags) processing. The author stresses that its application is fraught with a whole range of quite specific methodological and purely technical problems, in particular, screening out bots and other ways of traffic manipulation. Against this backdrop, the author advocates further improvement in the methods of studying digital diplomacy by fostering a culture of data analytics and making a more active use of developments from other disciplines (philology, sociology, cultural studies, etc.).